2018
DOI: 10.1186/s12905-018-0579-z
|View full text |Cite
|
Sign up to set email alerts
|

Low uptake of cervical cancer screening among HIV positive women in Gondar University referral hospital, Northwest Ethiopia: cross-sectional study design

Abstract: BackgroundCervical cancer is one of the leading causes of death in women worldwide. Majority of the cases are found in developing countries. The increasing risk of cervical cancer death and the high prevalence of human papilloma virus (HPV) infection in Human immuno-deficiency virus(HIV) positive women calls for determining the level of premalignant cervical cancer (Ca) screening uptake. So, this study aimed to assess the uptake of cervical cancer screening and its associated factors.MethodsAn institution base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
56
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 10 publications
13
56
4
Order By: Relevance
“…According to this study, majority of the respondents (81.8%) had heard about cervical cancer which is comparable with a similar study conducted in Gondar 87.7% (16) and significantly higher than another study conducted in Gondar (49.6%) (17) and 56.2% in Nigeria (20). Those who had heard about cervical cancer screening in this study were 76.1%, which is higher than 37.8% from a study in Gondar (17), 42.7% in Addis Ababa (25) and 34.5% in Nigeria (20). The source of information in the majority of the cases was health personnel which was similar to other study conducted in Addis Ababa (18).…”
Section: Discussionsupporting
confidence: 86%
“…According to this study, majority of the respondents (81.8%) had heard about cervical cancer which is comparable with a similar study conducted in Gondar 87.7% (16) and significantly higher than another study conducted in Gondar (49.6%) (17) and 56.2% in Nigeria (20). Those who had heard about cervical cancer screening in this study were 76.1%, which is higher than 37.8% from a study in Gondar (17), 42.7% in Addis Ababa (25) and 34.5% in Nigeria (20). The source of information in the majority of the cases was health personnel which was similar to other study conducted in Addis Ababa (18).…”
Section: Discussionsupporting
confidence: 86%
“…Studies have also been conducted to assess the therapeutic effectiveness of HPV vaccinations in the population of immunosuppressed patients [28].…”
Section: Primary Preventionmentioning
confidence: 99%
“…The uptake of cervical screening in underprivileged countries is clearly even lower. Nega et al [28] reported a 10% lifetime uptake of cervical screening in Ethiopia among HIV positive females, and 93.4% of those were only screened after the diagnosis of HIV.…”
Section: Secondary Preventionmentioning
confidence: 99%
“…Cervical cancer is one of the most common causes of cancer death in women worldwide [1,2]. Incidence and mortality rates have decreased in high-resource countries.…”
Section: Introductionmentioning
confidence: 99%